Interest and Good Faith Principle in Private Law Relationships (International Journal of Psychosocial Rehabilitation, 2020)
Currently, the study of interest in civil legal relations in terms of good faith is highly relevant, as is the issue of the objective interrelation between the interests balance and good faith. The article describes good faith in the context of legal interest-free implementation possibilities stipulated by law and considers various doctrinal and law-enforcement approaches to good faith principle implementation. The aim is to show interrelation and interdependence of legal interest and good faith, as the latter allows establishing some common boundaries for egoistic behavior of subjects involved in civil legal relationships. The key methods are formal juridical, comparative legal, and systemic ones, as well as other general and specific research methods. The authors conclude that the legal framework of the good faith principle is implemented in an ambivalent manner in common practice. So the bona fide is transformed depending on the circumstances akin to moral categories, while the bona fide principle is a juridical one that determines the critical importance of judicial discretion when stating the good or bad faith of a dispute subject.